Development and Evaluation of Digital Learning Materials for Arabic Reading Skills Using a Scientific Approach in Islamic Elementary Schools - Malikh, Majda Qudsiyatul; Mubaligh, Ahmad; Fitriani, Laily (STAI Syaichona Moh. Cholil Bangkalan, 2025)
Mastering maharah qiraah in Arabic learning is crucial as it is the gateway to understanding Arabic texts, which are key sources of Islamic knowledge. The scientific approach has enhanced students' comprehension, making developing effective teaching materials essential. This study develops and evaluates